PERANCANGAN DAN PENERAPAN COMPUTER BASED TEST (CBT) PADA SMK MUHAMMADIYAH KRAGILAN - Ely Nuryani; Wawan Suandi (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
In education field, examinations have become one way to measure the level of student achievement at school. Examinations that are usually used in schools such as daily/weekly/monthly exams, midterm exams (UTS) and final semester examinations (UAS). By using the exam, both students and teachers can evaluate each other about their teaching and learning activities. The examination model used so far is a conventional method model using paper-based tests. Traditional methods still have many disadvantages so other methods are needed to create efficiency, effectiveness, security, accuracy, and fast testing system. Another model that has been applied in school student test activities is the Computer Based Test (CBT Method). This method is proven to improve efficiency and effectiveness in the exam. Unfortunately, this new approach is only applied to national examination activities and has not been evenly distributed throughout the school. To use it in all the exam processes such as daily/weekly/monthly exams, midterm exams (UTS) and final semester examinations (UAS), this research uses waterfall metod was conducted at the Muhammadiyah Kragilan. The goal to be achieved is the creation of alternative test methods that can be used by partner schools that are more efficient, more effective, safer, more accurate and faster than the old test method